The Effect of Work Environment and Work Discipline on Employee Performance of PT Cibubur Indah Motor - Nur Indriyani, Siwi; Ike Irawati (Krisnadwipayana International Journal of Management Studies, 2025)
The purpose of this study is to analyze the influence of the Work Enviroment and Work Discipline on the Employee Performance of PT. Cibubur Indah Motor. This type of research is included in the category of casual associative quantitative research. The source of research data is primary data using a questionnaire with a Likert point scale of 5. The sampling technique used is saturated sampling. This research was conducted at PT. Cibubur Indah Motor. The analysis technique used in this study is multiple Linear Regression. The results of the analysis show that the Work Enviroment and Work Discipline both play a role